2017
DOI: 10.6018/analesps.34.1.266201
|View full text |Cite
|
Sign up to set email alerts
|

Independent and Interdependent? Agentic and Communal? Self-construals of People Fused with a Group

Abstract: Título: ¿Independiente e interdependiente? ¿Agencial y comunal? Autoconceptos de personas fusionadas con un grupo. Resumen: Se llevaron a cabo cuatro estudios para examinar cómo la auto identidad y la fusión grupal se relacionan con los autoconceptos, la autopercepción de rasgos agentes y comunales y el deseo de autocomprobación grupal. En el estudio 1 (N1 = 244), se examinó la fusión de identidad en relación con el país y el género, mientras que en los estudios 2 (N2 = 164) y 3 (N3 = 166) las relaciones de lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
(53 reference statements)
1
9
0
3
Order By: Relevance
“…We point out that low internal consistencies of the interdependent self-construal measure we found in both studies (Study 1:0.56, Study 2:0.62) should be given caution. Previous studies have also reported relatively low internal consistencies gauging interdependent self-construal (e.g., alphas = 0.63,0.64; Rohmann et al, 2012 ; Besta, 2018 ) alarming researchers for conducting similar future studies using such a measure. Despite the low Cronbach’s alphas, the interdependent self-construal highly correlated with the inter-personal closeness measure in our design (Study 1: r = 0.3 Study 2: r = 0.32) to form a composite social connectedness variable.…”
Section: Studymentioning
confidence: 94%
“…We point out that low internal consistencies of the interdependent self-construal measure we found in both studies (Study 1:0.56, Study 2:0.62) should be given caution. Previous studies have also reported relatively low internal consistencies gauging interdependent self-construal (e.g., alphas = 0.63,0.64; Rohmann et al, 2012 ; Besta, 2018 ) alarming researchers for conducting similar future studies using such a measure. Despite the low Cronbach’s alphas, the interdependent self-construal highly correlated with the inter-personal closeness measure in our design (Study 1: r = 0.3 Study 2: r = 0.32) to form a composite social connectedness variable.…”
Section: Studymentioning
confidence: 94%
“…It is described as a visceral feeling of unity with the group in which the personal self and the social self merge; thus, the boundary between both identities becomes permeable. The result is a strong union within the group, even though the identity of the personal self and the social self maintain a certain degree of independence (Besta, 2017).…”
Section: Identity Fusionmentioning
confidence: 99%
“…As a construct, identity fusion is associated with relational ties (feelings toward individual group members) and collective ties (feelings toward the group; see, e.g., Gómez et al, 2011aGómez et al, , 2020, with which a perceived connection and reciprocal strength are created between personal identity and group identity (Gómez et al, 2011a;Besta, 2018). Because of this strong unity with the group, fused individuals represent other group members as if they were their relatives (Whitehouse and Lanman, 2014;Swann et al, 2014a;Robert et al, 2019), this feeling of close bonding would be one of the main motivators of extreme pro-group behavior (see, e.g., Buhrmester and Swann, 2015;Fredman et al, 2015;Swann and Buhrmester, 2015).…”
Section: Introductionmentioning
confidence: 99%